Effects of phenol on the growth of Vigna angularis - Mustapha, Siti Roslina (2015)
Rapid industrialisation since the recent past years has led to the increasing number of pollutions from industrial wastes, with phenol as one of the organic pollutant produced. Phytoremediation is one of the effective techniques available to clean up pollutant in situ by using plants as the main agent to absorb pollutants from targeted sites. Vigna angularis, which is a legume from Fabaceae family, is an annual plant that can be found mainly in East Asia and Himalaya countries such as Japan, and Malaysia. In this study, an experiment was conducted to investigate effects phenol had on V. angularis, and the plant’s ability to absorb phenol contain in 4 L distilled water. Plants were exposed to different concentrations of phenol of 0.04, 0.05, 0.2, 0.3, and 0.4 g/L for 8 days and phenol remaining in the water was also being measured daily by using 4-aminoantipyrene assay method. The observations on changes on morphology of plants were made and followed by determination of rate of phenol degradation by plants. Changes on plants such as yellowing of leaves, changes of colour of roots from white to brown, and stems became droopy were recorded. The results obtained showed that V. angularis was able to tolerate variations of phenol concentrations, and can uptake 100% of phenol in the water for all concentrations with different rate of degaradations, except for in 0.4 g/L phenol.